Executive Summary & Final Report - Task Force on Equity, Diversity, and Inclusion of the Lester B. Pearson School Board (2021)
The purpose of this document is to present the results of deliberations and evidence-based recommendations of the Task Force of Lester B. Pearson School Board (LBPSB) on Diversity, Equity and Inclusion.

Prestation de services aux élèves ayant des besoins particuliers dans les écoles publiques anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Au Québec, un nombre croissant d’élèves sont identifiés comme ayant des besoins particuliers et on estime actuellement que cette population représente un élève sur cinq (20,4 %) dans le système scolaire public (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Keywords: Official Language Minority Community (OLMC)

Provision of Services to Special Needs Students in Quebec's English-language Public Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
In Quebec, a growing number of students are identified as having special needs, and it is currently estimated that this population represents one in five students (20.4%) in the public school system (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

ELAN (English-Language Arts Network) est heureux d’annoncer le lancement du programme de subventions Artistes Inspire (AI), soit un investissement de 2,2 millions de dollars destiné à créer des activités artistiques et culturelles dans les écoles de langue officielle en situation minoritaire au Québec - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

ELAN launches ArtistsInspire Grants (AIG), a $2.2 Million Investment for Quebec Official-language Minority Schools to Create Arts and Cultural Opportunities - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

Were is the Community Consultation? : Statement on School Closures - Quebec Federation of Home and School Associations (QFHSA) (2019)

Shutdown of Riverdale Destabilizing and Ill-advised : QCGN - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Home and Schools 1945-2019 - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

Resolution 2018-01 : Healthy Sleep and Late School Start Time - Quebec Federation of Home and School Associations (QFHSA) (2018)

Presentation to the Committee on Culture and Education on Bill 86 - Duszara, Walter; Chambers, Geoffrey; Maldoff, Eric; Martin-Laforge, Sylvia (2017)

Culture in the Schools - Application Guide - English Language Arts Network (ELAN) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

Bill 86 Tramples on Minority Rights and Should be Scrapped - Quebec Community Groups Network (QCGN) (2016)

Brief to the Committee on Culture and Education : Quebec and the Minority Language Educational Rights and Canada’s English Linguistic Minority Communities: A New Partnership - Quebec Community Groups Network (QCGN) (2016)
Voting in elections is an intrinsic right for all Quebecers. It is beyond democratic tradition for government to capriciously remove these rights without a pressing and substantial reason. Quebec’s English public school system is a key institution of the English-speaking community of Quebec, a linguistic minority community. The management and control of these institutions is a matter of governance subject to minority language educational rights contained in the Canadian Charter of Rights and Freedoms, and Quebec’s democratic tradition, expressed in the political rights guaranteed by the Quebec Charter of Human Rights and Freedoms.
Keywords: Official Language Minority Community (OLMC)

Mémoire à la Commission de la culture et de l’éducation : Le Québec et les droits à l’instruction dans la langue de la minorité, et les communautés d’expression anglaise en situation minoritaire au Canada : Un nouveau partenariat - Quebec Community Groups Network (QCGN) (2016)
Voter aux élections est un droit intrinsèque pour tous les Québécois. Mais le gouvernement va à l’encontre de sa tradition démocratique en révoquant capricieusement ce droit sans aucune raison impérieuse ou importante. Le système d’écoles publiques anglophones du Québec est une institution qui joue un rôle clé au sein de la communauté d’expression anglaise de la province — une communauté linguistique en situation minoritaire. La gestion et le contrôle de ces institutions sont une question de gouvernance qui touche les droits à l’instruction dans la langue de la minorité, ces droits étant enchâssés dans la Charte canadienne des droits et libertés et dans la tradition démocratique du Québec, ainsi qu’exprimés dans les droits politiques garantis par la Charte des droits et libertés de la personne du Québec. Le gouvernement du Québec a le devoir de reconnaître sa communauté linguistique minoritaire et de travailler en partenariat avec elle afin de garantir la gestion et le contrôle efficaces du système d’écoles publiques anglophones.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

Brief Addressed to the Committee on Culture and Education and Bill 56 : An Act to Prevent and Deal with Bullying and Violence in Schools - Quebec Federation of Home and School Associations (QFHSA) (2012)
The Quebec Federation of Home and School Associations (QFHSA) welcomes the opportunity to comment on Bill 56, An Act to prevent and deal with bullying and violence in schools.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

Un mémoire à l'intention de la Commission de la culture et de l’éducation : portant sur le projet de loi no 56 : Loi visant à lutter contre l’intimidation et la violence à l’école - Quebec Federation of Home and School Associations (QFHSA) (2012)
La Fédération Québécoise des Associations Foyers-Écoles (FQAFÉ) accueille l’opportunité de pouvoir commenter le projet de loi 56, intitulé Loi visant à lutter contre l’intimidation et la violence à l’école.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2010)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2009)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2009)

Entry Island School Yearbook - Entry Island School (2008)

Entry Island School Yearbook - Entry Island School (2004)

The Schools of Entry Island - Entry Island Historical Museum (2003)

Entry Island School Yearbook - Entry Island School (2002)

Entry Island School Yearbook - Entry Island School (2001)

Grosse-Ile High School - Grosse-Ile High School (2000)